Spatial Disparities and Policy Effectiveness in Azerbaijan's Regional Development - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2025)
This study assesses the design, implementation, and outcomes of the State Program for the Socio-Economic Development of the Regions of the Republic of Azerbaijan, the country's most comprehensive long-term development initiative spanning 2004-2023. Drawing on official statistical data and fiscal records, the paper evaluates four consecutive program cycles and complementary urban development schemes to determine their effectiveness in promoting balanced regional growth, reducing spatial disparities, and fostering economic diversification. Findings reveal that despite cumulative investments of approximately 92.2 billion Azerbaijani manats, regional inequality has not diminished. Economic activity remains overwhelmingly concentrated in the Baku-Absheron area, which generates over 80 percent of GDP while covering just 2.5 percent of the country's territory. The analysis demonstrates that regional policy outcomes have closely followed the cyclical pattern of hydrocarbon revenues, with the bulk of financing disbursed during oil-boom periods. The study also identifies the persistent procyclical character of public expenditure, weak institutional decentralization, and limited private sector engagement as key constraints undermining the program's developmental impact. The paper concludes that Azerbaijan's regional development strategy has achieved partial infrastructural improvements but failed to alter the highly centralized spatial structure of its economy. Future policies should prioritize institutional reforms, fiscal diversification, and enhanced regional autonomy to ensure inclusive, sustainable, and post-oil development
Keywords: R58; 330; Azerbaijan; Regional Development; Spatial Inequality; Resource Dependence; Oil Revenues; Fiscal Decentralization; Economic Diversification; Development Policy; Development Policy; State Programs